Misconception Reduction by Implementing Contextual Teaching and Learning (CTL) Approach on Salt Hydrolysis Material in Grade XI at SMA 1 Palasa - Moh. Raisul; Tahril Tahril; Afadil Afadil (Jurnal Akademika Kimia, 2020)
Misconception is a conception of someone who is not in accordance with the scientific concept recognized by experts. Student’s who experience misconceptions will make mistakes in understanding concept’s and occur continuously. This study aimed to determine the percentage of reduction of students’ misconception in grade XI SMA 1 Palasa on salt hydrolysis by implementing contextual teaching and learning (CTL) approach. This study was a quantitative descriptive study with the number of samples of 2 classes, that’s Class XI Science A consisted of 22 students, and Class XI Science B consisted of 22 students. The instrument test was a reasoned multiple choice test accompanied by a certainty of response index (CRI) consisting of 20 items. The results showed that the percentages of the average reduction of students’ misconceptions in the class XI science A and in the class XI science B on salt hydrolysis with contextual teaching and learning (CTL) approach were 19.6 and 9.8%, respectively.